2007
DOI: 10.2341/06-39
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Curing Rate of Resin Composite on the Bond Strength to Dentin

Abstract: SUMMARYThis study determined whether the strength with which resin composite bonds to dentin is influenced by variations in the curing rate of resin composites. Resin composites were bonded to the dentin of extracted human molars. Adhesive (AdheSE, Ivoclar Vivadent) was applied and cured (10 seconds @ 1000 mW/cm 2 ) for all groups. A split Teflon mold was clamped to the treated dentin surface and filled with resin composite. The rate of cure was varied, using one of four LED-curing units of different power den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
12
1
1
Order By: Relevance
“…20 Rapid polymerization may also result in the formation of high cross-linked short polymer chains. 21 The results of the current study show that all light energy densities achieve high CD and KHN values. Additionally, the light curing unit tip was directly in contact with the resin cement.…”
mentioning
confidence: 67%
“…20 Rapid polymerization may also result in the formation of high cross-linked short polymer chains. 21 The results of the current study show that all light energy densities achieve high CD and KHN values. Additionally, the light curing unit tip was directly in contact with the resin cement.…”
mentioning
confidence: 67%
“…When the distance between the curing light tip and cavity wall increases, light intensity reaching the adhesive surface decreases 9) . It has been demonstrated that reduced light intensity causes lower bond strengths between self-etch adhesives and dentin 10) . In addition, after the light irradiation of adhesives at a reduced light intensity, the top surface of the adhesive is covered with a relatively thick, uncured adhesive layer due to the oxygen inhibition 11) .…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that in light-cured resin composites, the photoinitiator used requires a certain amount of light energy to produce a certain number of free radicals 15) . To overcome this problem, an extension of irradiation time or use of high-light-intensity curing units might be effective in increasing the degree of polymerization of adhesive resins 11) . However, an extension of irradiation time is tantamount to prolonged operation time, and that irradiation with high light intensity elevates the temperature during adhesive polymerization 16,17) .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study suggested that airblowing suitable for self-etching one-step (all-in-one adhesive) systems depended upon the type of solvent contained in the system 8) . Further on factors that influence bond strength, there are several studies which reported on the effect of light intensity for filled resin composites on their bond strengths to tooth substrates [9][10][11] . Benetti et al 11) investigated the influence of variations in the curing rate of resin composites on the bond strength of resin composites to dentin, and concluded that only power density -but not curing mode, resin composite material, nor mode of aging -significantly affected shear bond strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation